Profiling of Histone Modifications Reveals Epigenomic Dynamics During Abdominal Aortic Aneurysm Formation in Mouse Models - Greenway, Jacob; Gilreath, Nicole; Patel, Sagar; Horimatsu, Tetsuo; Moses, Mary; Kim, David; Reid, Lauren; Ogbi, Mourad; Shi, Yang; Lu, Xin-Yun; Shukla, Mrinal; Lee, Richard; et al. (Frontiers in Cardiovascular Medicine, 2020)
Introduction: Abdominal aortic aneurysms (AAA) are characterized by localized inflammation, extracellular matrix degradation, and apoptosis of smooth muscle cells, which together lead to progressive and irreversible aortic dilation. Major risk factors for AAA include smoking and aging, both of which prominently alter gene expression via epigenetic mechanisms, including histone methylation (me) and acetylation (ac). However, little is known about epigenomic dynamics during AAA formation. Here, we profiled histone modification patterns in aortic tissues during AAA formation in two distinct mouse models; 1) angiotensin II (AngII) infusion in low density lipoprotein receptor (LDLR) knockout (KO) mice, and 2) calcium chloride (CaCl2) application in wild type mice. Methods and Results: AAA formed in both models, in conjunction with enhanced macrophage infiltration, elastin degradation and matrix metalloproteinases expression as evaluated by immunohistochemistry. To investigate the histone modification patterns during AAA formation, total histone proteins were extracted from AAA tissues, and histone H3 modifications were quantified using profiling kits. Intriguingly, we observed dynamic changes in histone H3 modifications of lysine (K) residues at different time points during AAA formation. In mature aneurysmal tissues at 3 weeks after AngII infusion, we detected reduced K4/K27/K36 monomethylation, K9 trimethylation K9, and K9/K56 acetylation (<70%), and increased K4 trimethylation (>130%). Conversely, in CaCl2-induced AAA, K4/K9/K27/K36/K79 monomethylation and K9/K18/K56 acetylation were reduced in AAA tissues, whereas K27 di-/tri-methylation and K14 acetylation were upregulated. Interestingly, K4/K27/K36 monomethylation, K9 trimethylation, and K9/K56 acetylation were commonly downregulated in both animal models, while no H3 modifications were uniformly upregulated. Western blot of AAA tissues confirmed markedly reduced levels of key H3 modifications, including H3K4me1, H3K9me3 and H3K56ac. Furthermore, pathway enrichment analysis using an integrative bioinformatics approach identified specific molecular pathways, including endocytosis, exon guidance and focal adhesion signaling, that may potentially be linked to these histone H3 modifications during AAA formation. Conclusions: Dynamic modifications of histone H3 occur during AAA formation in both animal models. We identified 6 discreet H3 modifications that are consistently downregulated in both models, suggesting a possible role in AAA pathobiology. Identifying the functional mechanisms may facilitate development of novel strategies for AAA prevention or treatment.